1995
DOI: 10.3109/00365549509019006
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter upsaliensis, C. sputorum sputorum and C. concisus as Common Causes of Diarrhoea in Swedish Children

Abstract: Scand J Infect Dis Downloaded from informahealthcare.com by Kungliga Tekniska Hogskolan on 08/10/15For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 4 publications
1
64
3
Order By: Relevance
“…Taken together, these findings suggest that a pathogenic role exists for at least certain subtypes of C. concisus strains. The need to establish whether C. concisus genomospecies 2 is an emerging human pathogen is evident in light of its high isolation rates in selected hospital settings (1,10,15,18,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings suggest that a pathogenic role exists for at least certain subtypes of C. concisus strains. The need to establish whether C. concisus genomospecies 2 is an emerging human pathogen is evident in light of its high isolation rates in selected hospital settings (1,10,15,18,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been detected in fecal samples from both healthy (9,10,30) and diarrhetic patients (1,9,10,15,18,20,22,29,30). As a consequence, its primary pathogenic potential is uncertain.…”
mentioning
confidence: 99%
“…IBD is a chronic inflammation of the gastrointestinal tract, and the two major clinical forms are Crohn's disease (CD) and ulcerative colitis (UC). In addition to IBD, C. concisus has been associated with diarrhoeal disease; several studies have reported the isolation of C. concisus from diarrhoeal faecal samples (Lastovica, 2006;Lindblom et al, 1995;Nielsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…concisus strains were isolated from children with diarrhoea in different countries (Russell, 1995;Lindblom et al, 1995;le Roux & Lastovica, 1998), and are known to be most common in some patient subgroups, mainly children under 24 months of age and immunocompromised patients (Engberg et al, 2000;Lastovica & le Roux, 2000;Aabenhus et al, 2002).…”
Section: Introductionmentioning
confidence: 99%